Enhancer RNAs in transcriptional regulation: recent insights - Chen, Qi; Zeng, Yaxin; Kang, Jinjin; Hu, Minghui; Li, Nianle; Sun, Kun; Zhao, Yu (Frontiers in Cell and Developmental Biology, 2023)
Enhancers are a class of cis-regulatory elements in the genome that instruct the spatiotemporal transcriptional program. Last decade has witnessed an exploration of non-coding transcripts pervasively transcribed from active enhancers in diverse contexts, referred to as enhancer RNAs (eRNAs). Emerging evidence unequivocally suggests eRNAs are an important layer in transcriptional regulation. In this mini-review, we summarize the well-established regulatory models for eRNA actions and highlight the recent insights into the structure and chemical modifications of eRNAs underlying their functions. We also explore the potential roles of eRNAs in transcriptional condensates.